PRODUKTIVITAS SIFAT KIMIA DAGING DAN AIR BUAH ENAM JENIS KELAPA HIBRIDA - ELSJE T. TENDA; H. G. LENGKEY; MIFTAHORRACHMAN MIFTAHORRACHMAN; HELDERING TAMPAKE (Jurnal Penelitian Tanaman Industri, 1999)
Productivity, chemical characteristics of coconut meat and water of six coconut hybridsThis research was conducted in Kima Atas Research Station-North Sulawesi for 10 years (1988-1998). The altitude is 80 meters above sea level, with soil type young vulcanic and climate type Ri Oldeman. The ield experiment was designed as a randomized block design with 5 replications, the number of palms was each 12 for treatment planted at 9 m x 9 m tiangle. The treatment consisted of six hybrids viz: Raja Dwarf (GRA) x Mapanget Tall (DMT), Bali Yellow Dwarf (GKB) x Mapanget Tall (DMT), Bali Yellow Dwarf (GKB) x Takome Tall (DTE), Nias Yellow Dwarf (GKN) x Takome Tall (DTF), and GKN x DTA (Khina-1) with GKN x WAT (PB-121) as control. The observation was done on the time of lowering, coconut and copra production, resistence to Phytophthora and chemical characteistics of coconut meat and water. The results of the expeiment showed that the time of lowering of GRA x DMT, GKB x DMT and GKN x DTE hybrids were not sipificantly diferent from with Khrna-I and PB-121 as control. At the 9* year, the nuts production per palm per year of GKN x DTE and GKB x DTE hybids were higher compared to other hybrids, but from the 8-9* years. the copra production of four hybrids were higher than PB-121 and Khina-I. The hybrids GRA x DMT and GKB x DTE wee more esistant to Phytophthora. The protein and oil content per palm of four hybids and Khina-1 wee better than that of PB-121.